Anatomia do desenvolvimento floral de Cassia multijuga Rich. (Leguminosae-Caesalpinoidae) - Guimarães, Delphos José; Fontenelle, Gerusa Brunow; Oliveira, Benedicto Antonio Duarte De [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 1984)
In the anatomical study of the flowers, Cassia multijuga our attention was called to the following occurencis the not simultaneous development of floral verticils; the presence of nectariferous tissue in the friezed side of the anthers; simultaneous development of the sporogenicus cells in all of the seven anthers, pluricell hair receptacle containing a substance rich in sugar; the presence of fertile-polen in all of the anthers; sclerified extracts under the epidermis of the anthers hindering the rimose dehiscense.

No estudo anatômico da flor de Cassia muitijuga Rich., chamou-nos atenção as seguintes ocorrências: desenvolvimento não simultâneo dos verticilos florais; presença de tecido nectarífero nos frisos laterais das anteras; desenvolvimento simultâneo das células esporogênicas em todas as sete anteras; pêlos pluricelulares de receptáculo com conteúdo rico em açúcar; presença de pólen fértil em todas as anteras; estratos esclerificados abaixo da epiderme da antera, o que impede a deiscência rimosa.